Modelling and simulation of vehicle movements at signalised road junctions - Liu, Jialin (2015)
Signalised road junctions is widely used in urban area to increase safety level and minimise conflicts between vehicles. Modelling and simulating the vehicle movements is able to help understanding the vehicle behaviour at the road junction for optimising the junction layout and signal set up. This paper presents a study about vehicle movements at different types of signalised road junctions. The results about the safety level of the road and vehicle travel time are tested when signal control strategies are changed. Field observation is conducted to record realistic traffic movements at junctions and the traffic volume and signal timing data are extracted. With the help of computer simulation, junctions are modelled for capacity and safety assessment by changing signal timing type from permissive to protected right-turn mode.